Physiological Responses of Pacific White Shrimp Litopenaeus vannamei to Temperature Fluctuation in Low-Salinity Water - Wang, Zhenlu; Qu, Yuexin; Yan, Muting; Li, Junyi; Zou, Jixing; Fan, Lanfen (Frontiers in Physiology, 2019)
Temperature is a significant environmental factor in aquaculture. To investigate the physiological responses during temperature fluctuation (28~13°C), experimental shrimps (Litopenaeus vannamei) were treated with gradual cooling from acclimation temperature (AT, 28°C) to 13°C with a cooling rate of 7.5°C/day and rose back to 28°C at the same rate after 13°C for 24 h. Hepatopancreas histological changes, plasma metabolites concentrations, relative mRNA expression of unfolded protein response (UPR) pathway and apoptosis in hepatopancreas and hemocyte were investigated. The results showed that with the decline of temperature, the number and volume of the secretory cells in hepatopancreas increased significantly, the tubule lumen appeared dilatated, and the epithelial cell layer became thinner. The contents of glucose (Glu) significantly decreased to the minimum value of 13°C for 24 h. The contents of triglyceride (TG), total cholesterol (TC), and total protein (TP) increased and reached the peak of 13°C for 24 h. Alkaline phosphatase (ALP) and alanine aminotransferase (ALT) activities in plasma reached the lowest and highest value in 13°C, respectively. The expressions of all genes related to UPR and apoptosis in the hepatopancreas and hemocytes were significantly changed during the cooling process and reached the highest level of 13 and 13°C for 24 h, respectively. During re-warming stage, the histopathological symptoms got remission and each of the plasma metabolite concentrations and gene expressions returned to AT levels. These results revealed that pacific white shrimp can adapt to a certain level of temperature fluctuation by self-regulation.